Extraction of chlorophyll concentration maps from AOTF hyperspectral imagery - Zolotukhina, Anastasia; Machikhin, Alexander; Guryleva, Anastasia; Gresis, Valeriya; Tedeeva, Victoriya (Frontiers in Environmental Science, 2023)
Remote measurement of chlorophyll concentration in leaves is highly important for multiple biological and agricultural applications. Due to precise, fast and arbitrary spectral tuning, acousto-optic (AO) imagers provide highly optimized data acquisition and processing. In this study, we demonstrate the feasibility to extract the distribution of chlorophyll content from AO hyperspectral data cubes. We collected spectral images of soybean leaves of 5 cultivars in the range 450-850 nm, calculated 14 different chlorophyll indices (CI), evaluated absolute value of chlorophyll concentration and compared it with well-established spectroscopic measurements. We found the most suitable CI and calculated chlorophyll maps from AO hyperspectral imaginary. This study exhibits high potential of AO imaging for real-time chlorophyll mapping.